Long-Acting Injectable Antipsychotics: A Systematic Review of Their Non-Systemic Adverse Effect Profile - Zolezzi M (Dove Medical Press, 2021)
Monica Zolezzi,1 Rawan Abouelhassan,1 Yassin Eltorki,2 Peter M Haddad,2 Mahtab Noorizadeh1 1College of Pharmacy, QU Health, Qatar University, Doha, Qatar; 2Mental Health Hospital, Hamad Medical Corporation, Doha, QatarCorrespondence: Monica ZolezziCollege of Pharmacy, Qatar University, PO Box 2713, Doha, QatarEmail mzolezzi@qu.edu.qaIntroduction: Long acting injectable (LAI) antipsychotics are commonly used in the treatment of schizophrenia to improve adherence and clinical outcomes. Concerns have been reported in relation to their non-systemic or injection site adverse effect profile. As such, this study aims to review and evaluate all evidence reporting injection site adverse effects with LAI antipsychotics.Methods: An electronic search was systematically conducted through four databases (PubMed, Embase, SCOPUS, Cochrane) in order to identify studies investigating injection-site reactions associated with LAI antipsychotics. Unpublished studies such as conference proceedings and clinical trial registries were also searched. The search was limited to literature published in English without year limits.Results: Of a total of 189 citations that were identified from the electronic database search, 12 were selected for inclusion in this review. Various injection site reactions were reported in these studies, including pain, bleeding, and swelling. Overall, the studies reported a low incidence of these injection site reactions. Only a minority of the included articles compared injection site reactions between different LAI antipsychotics.Conclusion: Injection site pain was the most commonly reported injection site adverse effect across all articles reviewed. The low incidence of injection site adverse effects associated with LAI antipsychotics indicates that these formulations appear to be well tolerated by patients. More head-to-head trials comparing second generation LAI antipsychotics are needed.Keywords: intramuscular preparations, depot antipsychotics, injection site adverse effects